INCREASING STUDENTS’ VOCABULARY BY USING LIST-GROUP-LABEL STRATEGY AT THE SEVENTH GRADE OF MTs DDI DARUL ULUM KALANGKANGAN - Moh Firmansyah (Jurnal Madako Education, 2019)
This research aims to find out whether the use of List-Group-Label Strategy can increase students’ vocabulary at the seventh grade of MTs DDI Darul Ulum kalangkangan. This research design belongs to a quasi-experimental research. There were two classes, namely VII A as control class (without List-Group-Label Strategy) with the total number of 23 students and VII B as experiment class (taught by List-Group-Label Strategy) with the total number of 22 students. The researcher gave pre-test and post-test to both groups. The researcher used SPPS 16.0 program to analyze the data. The result of data analysis showed that List-Group-Label strategy give a significant effect to the increasing students vocabulary specially noun. The mean score of post-test experiment (65.4091) was higher than the mean score of post-test control (49.6087). Then, the testing hypothesis showed that the value of score T-test is greater than Ttable (-2.862 > 1.681). In conclusion, the application of List-Group-Label strategy is effective to increasing students’ vocabulary especially noun. Key words: Increasing, noun, and List-Group-Label.